VD_FINDINFO Jug / 2012 / 267 vom 16. Mai 2012 - VD Tribunal cantonal (2012)
AGGRAVATION DE LA PEINE, FIXATION DE LA PEINE, PEINE PRIVATIVE DE LIBERTÉ | 43 CP, 44 CP, 47 CP, 19 al. 1 LStup, 19 ch. 2 LStup